Plan de exportación de manteca de cacao para el centro de acopio comunitario Santa Rosa, provincia de El Oro - Castillo Ordinola, Erika Tatiana (2015)
This project's main integrator cooperate with the improvement of companies that exist in our purpose, transforming them into stable, profitable and globally recognized organization, bringing their product to foreign markets. In the first chapter all concepts or norms that are closely relate to the topic of the project is drawn up, these are backed by scientific journals, ensuring that their research is truthful and developed based on real fundamentals since the publication of articles in paper scientists is very rigorous. Also at this point it intervenes requirements matrix that has been made the object of study, and detected the lack of adequate personnel in charge of international business. The second chapter is the essence of the project, here the proposed research has been done on the basis of identified shortcomings in the organization described. The proposed theme is export plan cocoa butter of community storage center Santa Rosa province of El Oro association, creating new product lines developed with international certifications necessary that the plaintiff requires, in turn help advance the country's economy. There is also the timeline that will perform each of the steps when running the project to move towards the export of products with added value and contribute to the development of the productive matrix of the country. In the third chapter the viability or feasibility of the proposal is developed, technical, social, environmental and financial dimensions that increase the profitability of the direct and indirect beneficiaries is analyzed. In addition the means of funding is set to intervene in new export business.